1993
DOI: 10.1084/jem.178.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte extravasation into the pancreatic tissue in transgenic mice expressing interleukin 10 in the islets of Langerhans.

Abstract: SllmmAryTransgenic expression of interleukin 10 (IL-10) in the islets of Langerhans leads to a pronounced pancreatic inflammation, without inflammation of the islets of Langerhans and without diabetes. A scattered infiltration of macrophages (Mtk) precedes localized accumulations of CD4 + and CD8 + T lymphocytes, B lymphocytes, and Mtk. This recruitment of inflammatory cells to the pancreas is somewhat surprising, since the biological activities of IL-10 in vitro indicate that IL-10 is a powerful immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(96 citation statements)
references
References 47 publications
8
87
1
Order By: Relevance
“…There was a significant increase in frequency of CD8 ϩ T cells and B cells in IL-10.tsF-treated mice. This supports previous work, which has shown that IL-10 can promote the growth of activated CD8 ϩ cells (38,39) and that increased pancreatic infiltration of CD4 ϩ , CD8 ϩ T and B cells were observed in an IL-10 transgenic model in NOD mice (40,41). In contrast to both the transgenic NOD study and the results we present here, transgenic mice constitutively producing human IL-10 (400 -700 pg/ml in serum) were protected from the induction of EAE and failed to show histological evidence of CNS infiltration (42).…”
Section: Discussionsupporting
confidence: 79%
“…There was a significant increase in frequency of CD8 ϩ T cells and B cells in IL-10.tsF-treated mice. This supports previous work, which has shown that IL-10 can promote the growth of activated CD8 ϩ cells (38,39) and that increased pancreatic infiltration of CD4 ϩ , CD8 ϩ T and B cells were observed in an IL-10 transgenic model in NOD mice (40,41). In contrast to both the transgenic NOD study and the results we present here, transgenic mice constitutively producing human IL-10 (400 -700 pg/ml in serum) were protected from the induction of EAE and failed to show histological evidence of CNS infiltration (42).…”
Section: Discussionsupporting
confidence: 79%
“…In particular, the identity of the cells which may prime CD4 + T cells given the fact that CT26 do not express MHC class II and IL-10 was shown to prevent macrophage and dendritic cell accumulation in the vicinity of certain tumor models. 17, 27 The present data and previous evidence showing that IL-10 may act as a potent leukocyte chemoattractant in vivo 28 and in vitro 29 suggest that IL-10 may inhibit tumor cell growth by accelerating leukocyte recruitment to the site of injection. It can be hypothesized that once T cells reach the tumor target, they can be activated in situ to eliminate the tumor cells.…”
Section: Discussionsupporting
confidence: 51%
“…These data contrast with previous reports of the anti-inflammatory effect of IL-10 in in vivo models (37,53,54), and probably reflect the critical importance of context in cytokine behavior. Indeed, the effects of IL-10 in vivo, and on individual cell types, are not always anti-inflammatory (55)(56)(57). Down-modulation of the IL-1R2 decoy receptor in response to IL-10 is suggestive of priming for IL-1 responsiveness, while the general increase in degrading lysosomal activity, in association with LPS-induced expression of membrane bound and soluble pattern recognition molecules, is indicative of enhanced phagocytic bacterial clearance (Table I).…”
Section: Discussionmentioning
confidence: 99%